2015
DOI: 10.1111/cen3.12268
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐Seq data analysis identifies the comprehensive profile of in vivo interferon‐β‐stimulated genes in multiple sclerosis

Abstract: Objectives Interferon‐beta (IFNβ) is the most widely used drug for reducing the disease activity of multiple sclerosis (MS), although a considerable population of MS patients are refractory to IFNβ. To establish personalized therapy for MS, the molecular mechanism underlying the therapeutic effects of IFNβ in MS should be thoroughly characterized by aid of next‐generation sequencing technology. Methods To elucidate a comprehensive profile of in vivo IFNβ‐stimulated genes (ISGs) in MS patients, we analyzed a RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Our findings are further supported by the finding that SOCS3 deficiency in Ly6C + myeloid cells enhances experimental LPS-induced acute lung injury (53). Given that the genes GBP1, IFI44L, IFITM1, and ISG20 -found to be differentially upregulated in the monocytes of ARDS patients, particularly in the CD16 + subsetare known to be type I IFN inducible (35), it appears that SOCS3 deficiency in the monocytes of ARDS patients renders them more responsive to circulating levels of type I IFNs than to increased IL-6-mediated IFN-γ-like signaling. Similar expression of GBP2 (54), GABARAP (36), and LYN (55) in the monocytes of the 2 groups of subjects, genes typically associated with IFN-γ signaling, suggests absence of enhanced response to IFN-γ in the monocytes of ARDS patients.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our findings are further supported by the finding that SOCS3 deficiency in Ly6C + myeloid cells enhances experimental LPS-induced acute lung injury (53). Given that the genes GBP1, IFI44L, IFITM1, and ISG20 -found to be differentially upregulated in the monocytes of ARDS patients, particularly in the CD16 + subsetare known to be type I IFN inducible (35), it appears that SOCS3 deficiency in the monocytes of ARDS patients renders them more responsive to circulating levels of type I IFNs than to increased IL-6-mediated IFN-γ-like signaling. Similar expression of GBP2 (54), GABARAP (36), and LYN (55) in the monocytes of the 2 groups of subjects, genes typically associated with IFN-γ signaling, suggests absence of enhanced response to IFN-γ in the monocytes of ARDS patients.…”
Section: Discussionsupporting
confidence: 80%
“…Expression of GBP1 -which encodes a member of the family of guanylate-binding proteins (GBPs), with functions in host defense (33,34) was expressed at a higher level in CD16 + monocytes, and the expression of multiple ISGs was also higher in the cells of ARDS patients (Figure 4). Treatment of human monocytes with IFN-β was previously shown to upregulate genes such as GBP1, IFITs, and IFI44L (35). Some of these IFN-target genes (GBP1, IFITM1) were found to be preferentially upregulated in CD16 + monocytes.…”
Section: Resultsmentioning
confidence: 93%
“…lncRNA C21orf62-AS1 is abnormally expressed in chromophobe renal cell carcinoma, correlating with OS of patients [ 33 ]. Additionally, C21orf62-AS is stimulated by interferon-beta in patients with multiple sclerosis [ 34 ]. lncRNA MIR99AHG is significantly downregulated in colorectal cancer [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies recently published in the journal, Clinical and Experimental Neuroimmunology, might provide answers to these questions. 4,5 Using various bioinformatics tools, Satoh et al found previously unknown molecular networks or key molecules relevant to neuroimmunology research.…”
mentioning
confidence: 99%
“…Two studies recently published in the journal, Clinical and Experimental Neuroimmunology , might provide answers to these questions . Using various bioinformatics tools, Satoh et al.…”
mentioning
confidence: 99%